The presynaptic scaffolding protein piccolo organizes the readily releasable pool at the calyx of held - Parthier, Daniel; Kuner, Thomas; Körber, Christoph (The journal of physiology, 2018)
Key points Bassoon and Piccolo do not mediate basal synaptic vesicle release at a high-frequency synapse. Knockdown of Bassoon increases short-term depression at the calyx of Held. Both Bassoon and Piccolo have shared functions in synaptic vesicle replenishment during high-frequency synaptic transmission. Piccolo organizes the readily releasable pool of synaptic vesicles. It safeguards a fraction of them to be not immediately available for action potential-induced release. This enables the synapse to sustain high-frequency synaptic transmission over long periods. Abstract Synaptic vesicles (SVs) are released at the active zone (AZ), a specialized region of the presynaptic plasma membrane organized by a highly interconnected network of multidomain proteins called the cytomatrix of the active zone (CAZ). Two core components of the CAZ are the large, highly homologous scaffolding proteins Bassoon and Piccolo, whose function is not well understood. To investigate their role in synaptic transmission, we established the small hairpin RNA (shRNA)-mediated in vivo knockdown (KD) of Bassoon and Piccolo at the rat calyx of Held synapse. KD of Bassoon and Piccolo, separately or simultaneously, did not affect basic SV release. However, short-term depression (STD) was prominently increased by the KD of Bassoon, whereas KD of Piccolo only had a minor effect. The observed alterations in STD were readily explained by reduced SV replenishment in synapses deficient in either of the proteins. Thus, the regulation of SV refilling during ongoing synaptic activity is a shared function of Bassoon and Piccolo, although Bassoon appears to be more efficient. Moreover, we observed the recruitment of slowly-releasing SVs of the readily-releasable pool (RRP), which are normally not available for action potential-induced release, during high-frequency stimulation in Piccolo-deficient calyces. Therefore, the results obtained in the present study suggest a novel and specific role for Piccolo in the organization of the subpools of the RRP.